Molten o-H3PO4: A New Electrolyte for the Anodic Synthesis of Self-Organized Oxide Structures - WO3 Nanochannel Layers and Others - Altomare, Marco; Pfoch, Ole; Tighineanu, Alexei; Kirchgeorg, Robin; Lee, Kiyoung; Selli, Elena; Schmuki, Patrik (Journal of the American Chemical Society, 2015)
We introduce the use of pure molten ortho-phosphoric acid (o-H3PO4) as an electrolyte for self-organizing electrochemistry. This electrolyte allows for the formation of self-organized oxide architectures (one-dimensional nanotubes, nanochannels, nanopores) on metals such as tungsten that up to now were regarded as very difficult to grow self-ordered anodic oxide structures. In this work, we show particularly the fabrication of thick, vertically aligned tungsten oxide nanochannel layers, with pore diameter of ca. 10 nm and illustrate their potential use in some typical applications.
EAM Import::2019-03-12